2003
DOI: 10.1093/nar/gkg725
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme-mediated REV1 inhibition reduces the frequency of UV-induced mutations in the human HPRT gene

Abstract: In yeast, mutations induced by UV radiation are dependent on the function of the Rev1 gene product, a Y-family DNA polymerase that assists in translesion replication with potentially mutagenic consequences. Human REV1 has been cloned, but its role in mutagenesis and carcinogenesis remains obscure. To examine the role of REV1 in UV mutagenesis in human cells and to evaluate its potential as a therapeutic target to prevent such mutations, we developed a ribozyme that cleaves human REV1 mRNA in vitro. Stable expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…However, no significant difference was observed between REV1-depleted cells and control cells (data not shown), indicating that it is difficult to assess effects of Hsp90 inhibition on REV1 function using this assay. These results are consistent with previous observations, which showed that antisense or ribozyme-mediated suppression of REV1 levels significantly decreased UVinduced mutagenesis but had little effects on UV-induced cytotoxicity (8,12). Thus, the mutagenesis assay seems more sensitive to reduced REV1 protein levels compared with the cell survival assay.…”
Section: Resultssupporting
confidence: 93%
“…However, no significant difference was observed between REV1-depleted cells and control cells (data not shown), indicating that it is difficult to assess effects of Hsp90 inhibition on REV1 function using this assay. These results are consistent with previous observations, which showed that antisense or ribozyme-mediated suppression of REV1 levels significantly decreased UVinduced mutagenesis but had little effects on UV-induced cytotoxicity (8,12). Thus, the mutagenesis assay seems more sensitive to reduced REV1 protein levels compared with the cell survival assay.…”
Section: Resultssupporting
confidence: 93%
“…In DT40 cells REV1 not only facilitates Polf-dependent bypass, but also modifies the catalytic behavior of Polf, restraining its synthetic activity to ensure that it incorporates nucleotides in-frame with the damaged template [125]. Human cell lines expressing high levels of human REV1 antisense RNA or ribozyme exhibit a much reduced frequency of 6-thioguanine-resistant mutants induced by UV-irradiation or BPDE [122,126,127], indicating that REV1 in higher eukaryotic cells performs functions similar to its yeast homologs. This property has been confirmed in a different experimental system using RNA interference to down-regulate mouse REV1 [128].…”
Section: Rev1 Functions In Vivomentioning
confidence: 99%
“…We have reported that many of the mutations induced by DDP adducts seem to result from error-prone translesional DNA synthesis mediated by DNA polymerase and/or hREV1 (Wu et al, 2004;Okuda et al, 2005). Several investigators have reported previously that a loss of hREV1 function markedly reduces UV-induced hypoxanthine guanine phosphoribosyl transferase mutations in human cells engineered to contain reduced levels of hREV1 mRNA through the expression of an hREV1 antisense RNA (Gibbs et al, 2000) or a ribozyme that cleaves endogenous hREV1 mRNA (Clark et al, 2003). It has also been demonstrated that inactivation of the REV1 gene in chicken DT40 cells renders them hypersensitive to a wide variety of mutagens, including DDP (Simpson and Sale, 2003).…”
mentioning
confidence: 99%